Java Red Rice (Oryza sativa L.) Nutritional Value and Anthocyanin Profiles and Its Potential Role as Antioxidant and Anti-Diabetic - Ayu Tri Agustin; Anna Safitri; Fatchiyah Fatchiyah (Indonesian Journal of Chemistry, 2021)
This study investigates nutritional value, amino acid profile, and total anthocyanin in pigmented rice as an antioxidant and anti-diabetic agent. Six rice varieties were extracted using 0.1% HCl in methanol, namely four red rice, one black rice, and one white rice. Rice extract was used for proximate analysis and amino acid profiling. Total anthocyanin was measured and identified by ultraviolet-visible (UV-Vis) spectrophotometer and thin-layer chromatography (TLC). The antioxidant activity was determined using Ferric-reducing antioxidant power (FRAP) assay, and the α-amylase enzyme-inhibited by anthocyanin extract of red rice as anti-diabetic was measured. The study result showed that the proximate level (carbohydrate, protein, lipid, water, and ash) in pigmented rice was different. Cempo merah red rice is a source of amino acids, both essential and non-essential amino acids that act as good nutrition. The highest total anthocyanin level between red rice varieties of 10.87 mg/g was found in Aek sibundong red rice. High biological function activities as an antioxidant were indicated by Aek sibundong red rice with an IC50 value of 6.65 µg/mL. Aek sibundong red rice shows the lowest IC50 value of 144.46 µg/mL in anti-diabetic activity. Thus, Aek sibundong red rice may have the potential as α-amylase inhibitor for diabetes prevention.